Distance and height of attraction by walking and flying beetles to traps with simultaneous use of the aggregation pheromones from Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae) and Rhyzopertha dominica (F.) (Coleoptera: Bostrychidae). (December 2020) - Dissanayaka, D.M.S.K.; Sammani, A.M.P.; Wijayaratne, L.K.W.; Bamunuarachchige, T.C.; Morrison III, W.R.
Abstract: Adults of Tribolium castaneum (Herbst) and Rhyzopertha dominica (F.) biosynthesize aggregation pheromones 4, 8-dimethyldecanal and dominicalure-1/dominicalure-2, respectively. These pheromones are commonly used independently, and their simultaneous use has not been adequately studied. Furthermore, information on trapping flying R. dominica in pheromone traps is minimum. Therefore, the objectives were to evaluate distance of attraction of T. castaneum and R. dominica adults to traps having both pheromones, and height of R. dominica adult attraction to traps with its pheromone lure alone. In first experiment, both pheromones were deployed simultaneously inside a commercial pitfall trap. One-month-old 20 T. castaneum and R. dominica adults were released every 30 cm from the pheromone trap. The adults trapped were recorded at 4 and 24 h following their release. Adults of both species released were captured in higher percentages at 24 h than 4 h. At 30 cm distance, these values were 45.5% for T. castaneum and 10–12% for R. dominica for 24 h whereas they were 40.5% for T. castaneum and 5–7.5% for R. dominica following 4 h exposure. The maximum trap capture was at 30 cm for T. castaneum and 30–60 cm for R. dominica . In second experiment, a trap with two rubber septa containing dominicalure-1 and dominicalure-2 was placed at different heights inside cage, and R. dominica adults were released at the bottom. In each experiment, four replicates were tested. After 24 h, flying R. dominica adults were captured in progressively lower percentages as trap height increased up to 40 cm above the bottom of cage. Trap heights above 10 cm exhibited decreased trap capture of R. dominica compared to those at 3 cm. We conclude that simultaneous use of both aggregation pheromones better facilitates trapping of walking T. castaneum and R. dominica . Traps above 10 cm show decreased captures of flying R. dominica. Highlights: The aggregation pheromones of both walking T. castaneum and R. dominica attract individuals optimally 30–60 cm away. Flying R. dominica were captured optimally in traps deployed up to 10 cm above the ground by its aggregation pheromones. Use of more than one pheromone for trapping would resolve practical limitations with monitoring.